(untitled) (Journal of Medicine, 2012)
Probiotics are receiving increasing attention in the medical field. This is partly due to the recognition that microbial resistance to antibiotics presents a serious world-wide problem. In addition, fast growing insight into host-microbe interactions opened new routes in the development of rational alternatives in therapy and prevention of diseases as result of the complex procaryotic-eucaryotic evolutionary symphony. Consequently, long existing aspects of probiotics came into focus, and already provide exciting prospects. DOI: http://dx.doi.org/10.3329/jom.v13i1.10049 JOM 2012; 13(1): 55-59